Stella Batts : a case of the meanies - Sheinmel, Courtney (Sheinmel, Courtney. Stella Batts, 2012)
"Everyone is invited to a birthday party at her parent's candy store, except Stella Batts. She needs to figure out how to be a pleasant hostess when she's not on the guest list"--